Bacteriological profile and antibiotic sensitivity pattern in patients with Urinary tract infection - Subedi, N; Pudasaini, S (Journal of Pathology of Nepal, 2017)
Background: Urinary tract infection is one of the common bacterial infections seeking treatment in clinical practice. A variety of organisms are associated with UTI and the most common organisms are Escherichia coli and other coliforms. Bacteriological investigations of UTI are not complete without antibiotic sensitivity test of the isolate. The aim of this study is to determine the bacteriological profile and antibiotic sensitivity patterns and their disease association. Materials and methods: This study was conducted in Shankarapur Hospital over a period of one year. All cases of suspected UTI sent for urine culture and sensitivity test were evaluated in this study. Disease associated with UTI, bacteriological profile and antibiotic sensitivity patterns were evaluated. Results: A total of 974 cases were sent for urine culture and sensitivity test. The total culture positive cases were 165 (17.4%). The most common age group for culture positive test was 21- 30 years (33.3%) followed by 31- 40 years (25.5%). Female patients formed the majority of culture positive cases (84.8%) and E Coli (86.1%) was the most common organism isolated. Piperacillin- tazobactum and ceftriaxone were the most common antibiotic sensitive to the organisms. Simple uncomplicated UTI and PID were the most common indication for subjecting the patients to urine culture. Conclusion: UTI is most commonly seen in female of reproductive age group and the most common causative organism is E coli. Culture result and antibiogram helps the clinician for specific treatment of UTI.